Faktor-Faktor yang Mempengaruhi Tingkat Adopsi Peternak terhadap Program Upsus Siwab di Kecamatan Sambi, Kabupaten Boyolali - Budi Hasim Alyasin; Suwarto Suwarto; Sugihardjo Sugihardjo (AGRITEXTS: Journal of Agricultural Extension, 2020)
The Upsus Siwab (Special Efforts for Obligatory Pregnant Broodstok) Program is a program launched by the Director-General of Animal Husbandry and Health, Ministry of Agriculture to accelerate the acceleration of the target fulfillment of domestic beef cattle populations. The objective of the research is: 1) To study and analyze the adoption level of breeders in the Upsus Siwab program in Sambi District, Boyolali Regency, 2) To study or analyze what factors influencing the adoption rate of breeders in the Upsus Siwab program in Sambi District, Boyolali Regency. The basic method of this research was a quantitative method with survey techniques. The research location is in Sambi District, Boyolali Regency which is one of the implementing areas of the Upsus Siwab program. The total population of the study was 478 breeders who implemented the Upsus Siwab program. The sampling used a proportional random sampling technique with a sample size of 60 respondents. Data analysis used multiple linear regression analysis. The results showed that the adoption rate of breeders in the Siwab upsus program in Sambi District, Boyolali Regency was included in the high category with a percentage of 51.67%. Simultaneously or together variables of age, formal education, non-formal education, number of families, land area, number of livestock, livestock business environment significantly influenced the rate of adoption of the Upsus Siwab program in Sambi District, Boyolali Regency. Partially, the variables that had significant influence were the number of livestock (X6), other variables such as age (X1) formal education (X2), non-formal education (X3), number of families (X4), and land area (X5), and dummy environmental livestock business (δ) had no significant effect on the level of adoption of the Upsus Siwab program in Sambi District, Boyolali Regency.